2015
DOI: 10.1126/scisignal.aaa1977
|View full text |Cite
|
Sign up to set email alerts
|

Tandem phosphorylation within an intrinsically disordered region regulates ACTN4 function

Abstract: Phosphorylated residues occur preferentially in the intrinsically disordered regions of eukaryotic proteins. In the disordered N-terminal region of human α-actinin-4 (ACTN4), Tyr4 and Tyr31 are phosphorylated in cells stimulated with epidermal growth factor (EGF), and a mutant with phosphorylation-mimicking mutations of both tyrosines exhibits reduced interaction with actin in vitro. Cleavage of ACTN4 by m-calpain, a protease that in motile cells is predominantly activated at the rear, removes the Tyr4 site. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 62 publications
1
27
1
Order By: Relevance
“…Phosphoproteomic analysis revealed that phosphorylation of one site can enhance the phosphorylation of neighboring sites within ∼10 amino acids ( 49 ). Moreover, recent studies have found evidence for such phosphorylation priming in an actin cross-linking protein ( 50 ) and within the two tyrosines of the ITAM ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoproteomic analysis revealed that phosphorylation of one site can enhance the phosphorylation of neighboring sites within ∼10 amino acids ( 49 ). Moreover, recent studies have found evidence for such phosphorylation priming in an actin cross-linking protein ( 50 ) and within the two tyrosines of the ITAM ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the CTs of α‐ and β‐tubulin are also IDRs that regulate microtubules via intermolecular interactions . Local charge, for example the phosphorylation state of a residue within the IDR or the IDP, is frequently associated with the control of conformation and serves as a regulatory switch for protein–protein interactions and functionality . In the case of the γ‐CT polypeptide, a Y > D substitution at a known in vivo phosphorylation site causes it to undergo global cooperative transitions between different conformational states.…”
Section: Discussionmentioning
confidence: 99%
“…One of the effects of phosphorylation on IDR could be transition of higher-order structures (10, 47, 48). Phosphorylation in IDR has been known to cause disorder-to-order or order-to-disorder transition.…”
Section: Discussionmentioning
confidence: 99%